Scope of work and contributions of female community health volunteers in Nepal’s healthcare sector: a qualitative study - Archana Shrestha; Biraj Man Karmacharya; Surakshya Kunwar; Sudim Sharma; Sabina Marasini; Anjali Joshi; Bandana Paneru; Akina Shrestha (BMJ Open)
Objectives To determine the perception of female community health volunteers (FCHVs) in terms of their scope of work, impact of work on their professional experiences and their coping strategies and stakeholders’ perception of FCHVs programme, their contribution to the health sector and its sustainability.Design A qualitative study involving in-depth interviews (IDIs) with FCHVs and key informant interviews (KIIs) with local stakeholders. All the interviews were conducted through telephone.Setting Six municipalities in Kavre district, Nepal.Participants 16 FCHVs participated in IDIs and 12 local stakeholders involving members of mother’s group, health workers and local ward representatives of the selected municipalities were involved in KIIs from May to August 2021.Results The FCHVs perceived a sense of workload because of their wide scope of work. The major challenges faced by FCHVs were limited allowances and incentives for their contribution, negative and judgemental attitudes, geographical challenges, multitasking, inadequate supply of health commodities and limited infrastructures for service delivery. Both the FCHVs and the stakeholders perceived the FCHV programme as one of the most effective programmes supporting the health system. However, they seem concerned about the sustainability of FCHVs programme. In addition, they indicated that the FCHVs could possibly alleviate the shortage of health workforce by providing preventive and promotive healthcare services at the grassroot level.Conclusion Our study showed a need for systematic and integrated health programme delivery packages thereby reducing additional workload and burden among FCHVs.